2008
DOI: 10.1038/ijo.2008.219
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviour and weight in children

Abstract: Objective:To test the hypothesis that quantitative variation in eating behaviour traits shows a graded association with weight in children.Design:Cross-sectional design in a community setting.Subjects:Data were from 406 families participating in the Physical Exercise and Appetite in CHildren Study (PEACHES) or the Twins Early Development Study (TEDS). Children were aged 7 to 9 years (PEACHES) and 9 to 12 years old (TEDS).Measurements:Weights and heights were measured by researchers. BMI SD-scores were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

64
335
12
31

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(442 citation statements)
references
References 44 publications
(53 reference statements)
64
335
12
31
Order By: Relevance
“…These findings are at odds with previous UK work, 17 which has shown systematic graded associations between eating behaviours measured by the CEBQ and adiposity. However, such studies have significantly larger sample sizes and our current samples are small.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are at odds with previous UK work, 17 which has shown systematic graded associations between eating behaviours measured by the CEBQ and adiposity. However, such studies have significantly larger sample sizes and our current samples are small.…”
Section: Discussioncontrasting
confidence: 99%
“…We hypothesised that 'food approach' child eating behaviours would be positively associated with child BMI, whereas 'food avoidant' behaviours would be negatively associated with child BMI in all samples. 16,17 It was hypothesised that WG parents would use lower levels of controlling feeding practices than WB parents, and that BAC parents would use the highest levels of these practices. It was hypothesised that WG children would show lower levels of 'food approach', and higher levels of 'food avoidant' behaviours than WB children, and that children of BAC parents in the UK would be reported to show higher food approach and lower food avoidance than either White European group.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that the prevalence of overweight and obesity in Beijing increased from 2004 to 2010, and already has become a serious public health concern that needs to be addressed. Parent-reported eating speed of children at home was significantly associated with childhood overweight, which was consistent with the results reported by previous studies conducted in children (8)(9)(10) and adults (17)(18)(19) . The present study further assessed the eating rate of pre-school children by actually observing their eating behaviours under the usual food-consuming environment in kindergartens.…”
Section: Discussionsupporting
confidence: 91%
“…Overeating, eating until full or having larger portion size of food also led to increase in energy intake and thus overweight or obesity (6,(13)(14)(15) . However, previous studies on the relationship between these eating behaviours and overweight were focused on parent-reported behaviours (8)(9)(10) or conducted in standardized laboratory settings or clinical research facilities (11,12,15) , and no information has yet been available on observed meal duration and excess energy intake of commonly consumed foods in daily life in pre-school children. Eating practices tend to be established early in life, and it is necessary to estimate the actual contributions of some unhealthy eating behaviours to childhood overweight in the context of children's usual food-consumption environment.…”
mentioning
confidence: 99%
“…There has been little previous work relating infant eating avidity to growth or weight gain, apart from one, which found associations between milk feeding vigour and concurrent skinfold thicknesses in healthy infants (11) as well as with BMI in the same infants at age 6 years (10) . A number of studies in childhood have found relationships between child eating behaviour and overweight or adiposity (26)(27)(28)(29) , but these were not prospective, making it difficult to distinguish cause and effect. One study has shown that child eating behaviours track through mid childhood (30) .…”
Section: Discussionmentioning
confidence: 99%